2020
DOI: 10.1139/cgj-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of pile groups subjected to horizontal loads

Abstract: This paper presents an analytical method for calculating the dynamic impedance of pile groups comprising an arbitrary number of cylindrical piles connected with a rigid cap. The solution allows consideration of ground waves due to pile vibration that propagate along both the horizontal and vertical planes, as well as the effect of the actual pile section geometry on the reaction from the surrounding soil. For that, we introduce a dynamic pile–soil–pile interaction factor that is defined on the basis of soil re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Chen et al studied the dynamic characteristics and damage law of subway station [21]. Other scholars have also undertaken a lot of research on the dynamic response of various structures and foundations under earthquake using shaking table test and found that the depth and compactness of soil, the existence of structures, and the input parameters of shaking excitation have obvious effects on site liquefaction and dynamic response of structures and soil [22][23][24][25][26][27][28][29][30]. However, the above studies are aimed at the terrigenous sands, and there are few studies on coral sand at present.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al studied the dynamic characteristics and damage law of subway station [21]. Other scholars have also undertaken a lot of research on the dynamic response of various structures and foundations under earthquake using shaking table test and found that the depth and compactness of soil, the existence of structures, and the input parameters of shaking excitation have obvious effects on site liquefaction and dynamic response of structures and soil [22][23][24][25][26][27][28][29][30]. However, the above studies are aimed at the terrigenous sands, and there are few studies on coral sand at present.…”
Section: Introductionmentioning
confidence: 99%
“…Design of structures acquires accounting for how foundations (e.g., piles and rigid footings) interact with soil subjected to dynamic loading such as seismic loads and machine vibrations 1–4 . The common approach to this problem considered the foundation soil as an elastic, homogeneous, and isotropic half‐space, commonly abbreviated as elastic half‐space, and assumed a specific distribution of contact stresses below the rigid foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Pile foundations are used to transfer static and dynamic loads to competent soil layers, which are commonly found below the groundwater table. Interaction of piles with their surrounding soil is particularly important for the analysis of dynamic soil‐foundation‐structure interaction problems; therefore, various approaches are proposed in the literature for modelling the response of piles subjected to harmonic loads . Early methods consider soil as single‐phase medium.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these refinements, certain limitations are inherited within the plane strain model: the contribution of pile base resistance to the dynamic response of the soil‐pile system, as well as the vertical stress gradient of the soil surrounding the pile shaft, cannot be explicitly considered. These shortcomings can be addressed by considering soil as full three‐dimensional continuum, but this comes at the expense of a rather complex formulation.…”
Section: Introductionmentioning
confidence: 99%